2015
DOI: 10.1007/s12031-015-0498-5
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-8 Mediates Amyloid-β-induced Apoptosis in Differentiated PC12 Cells

Abstract: The pathogenesis of Alzheimer's disease (AD) is very complex and there are currently no significant treatments for the disease. Caspase-8 is known to be involved in neuronal apoptosis. To explore a possible molecular mechanisms involved in AD pathology, this study investigated the effect of caspase-8 knockdown on amyloid-β 1-40 (Aβ1-40)-induced apoptosis in PC12 cells. The proliferation of PC12 cells was significantly inhibited in Aβ-treated cells, and a high fraction of the cells underwent apoptosis in a dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
(39 reference statements)
1
12
0
Order By: Relevance
“…A number of studies have indicated that EAPW plays a crucial role in the apoptotic process induced by Aβ42 (13,14,44). In the present study, we observed activation of caspase-8 and Bid processing (Fig.…”
Section: Disc Is Not Formed In Aβ42-treated Cellssupporting
confidence: 73%
See 1 more Smart Citation
“…A number of studies have indicated that EAPW plays a crucial role in the apoptotic process induced by Aβ42 (13,14,44). In the present study, we observed activation of caspase-8 and Bid processing (Fig.…”
Section: Disc Is Not Formed In Aβ42-treated Cellssupporting
confidence: 73%
“…Some studies have indicated that EAPW is elicited in Aβ-treated cells (12,44). This conclusion is usually based on activation of caspase-8, cleavage of Bid, upregulation of related proteins, and downregulation of EAPW-inhibiting proteins in the cells.…”
Section: Discussionmentioning
confidence: 99%
“…The neuronal toxicity of Aβ 1–40 is reflected in its ability to cause energy dysmetabolism, and induce cell damage and death (27,28). A number of previous studies used PC12 cells to investigate the molecular mechanisms underlying the development of degenerative diseases of the nervous system (2932). Therefore, the present study employed the PC12 cells that were damaged by Aβ 1–40 exposure as the cell model of AD and the significance of NAMPT in AD was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Some soluble A β oligomers, highly prone to aggregation and self-assemble to form a heterogeneous mixture of oligomers and protofibrils, are considered as the major neurotoxic species in AD [2022]. A β induced apoptosis occurs in the AD brain and plays a role in neuronal dysfunction and neurodegeneration, which contributes to the progression of AD [23]. In this study, A β 1–42 exposed PC12 cells were used to investigate the protection mechanism of Goutengsan in vitro and rats lateral cerebral ventricle injected with A β 1–42 was used in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Executioner caspases (caspase-3, caspase-6, and caspase-7) and upstream effector caspases (caspase-2, caspase-8, caspase-9, and caspase-10) are well known as mediators in AD brains [23]. Caspase-3 and caspase-9 may also be potential therapeutic targets for AD [17].…”
Section: Discussionmentioning
confidence: 99%